Surgical management of supratentorial and infratentorial epidural hematoma in Korea: three case reports - Su Young Yoon; Junepill Seok; Yook Kim; Jin Suk Lee; Jin Young Lee; Mou Seop Lee; Hong Rye Kim (Journal of Trauma and Injury)
Supratentorial and infratentorial epidural hematoma (SIEDH) is a rare but life-threatening complication following traumatic brain injury. However, the literature on SIEDH is sparse, consisting only of a few small series. Prompt diagnosis and the application of appropriate surgical techniques are crucial for the rapid and safe management of SIEDH. Herein, we present three cases of SIEDH treated at our institution, employing a range of surgical approaches.